STUDY OF THE COMBINATION OF FULL DISPLACEMENT COLUMN (FDC) AND LIGHT EMBANKMENT METHODS FOR SOFT SOIL IMPROVEMENT(CASE STUDY OF TOLL ROAD PROJECTS IN WEST SUMATERA PROVINCE) - Octafiansyah, Reyno
Infrastructure development in Indonesia often encounters existing conditions that require special handling, such as soft soil conditions. During the construction of the Toll Road in West Sumatra, soft soil (NSPT = 0) was also encountered with varying depths of 9 m – 12 m. Under these conditions, improvements have been made using the Full Displacement Column (FDC) method combined with the Load Transfer Platform (LTP) and geotextile. However, when the embankment was carried out at half of the design height, a slide occurred in the embankment material which was suspected to be due to failure of the embankment base due to the non-optimal load transfer system between FDC and LTP, water entering the embankment material which was predominantly sand, and hydrocompaction. In this study, alternatives for soft soil improvement were analyzed in the form of a combination of FDC systems and lightweight embankment materials (foam mortar). The results of modeling using the finite element method, the use of light embankment material can increase the value of safety factor (SF) in the FDC system with the most optimal conditions using LTP thickness of 0.5 m and 0.5 m light embankment (with fc light embankment 800 kPa). The settlement has fulfilled the requirements of <10 cm within 10 years.